2004
DOI: 10.1016/j.ijgo.2003.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Uterine diameters and endometrial thickness in patients with severe primary dysmenorrhea

Abstract: Intrauterine pressure throughout the cycle may be higher in dysmenorrheic women, which could hypothetically lead to uterine muscle hypertrophy. Additionally, possible changes in ovarian hormone levels together with changes in local microcirculation might have an effect on the endometrium w1-4x. Therefore, using B-mode ultrasonography, we investigated whether there are differences in uterine diameter and endometrial thickness between control women and women with severe primary dysmenorrhea (PD).Thirty-six women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In contrast to our findings, Zebitay et al ( 10 ) showed longer cervical length and greater cervical volume in young virgin patients with dysmenorrhea. Dmitrovic et al ( 16 ) found a positive correlation between uterine dimensions, endometrial thickness, and dysmenorrhea severity. The results of this study were not similar to those of Dmitrovic et al ( 16 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Zebitay et al ( 10 ) showed longer cervical length and greater cervical volume in young virgin patients with dysmenorrhea. Dmitrovic et al ( 16 ) found a positive correlation between uterine dimensions, endometrial thickness, and dysmenorrhea severity. The results of this study were not similar to those of Dmitrovic et al ( 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Dmitrovic et al ( 16 ) found a positive correlation between uterine dimensions, endometrial thickness, and dysmenorrhea severity. The results of this study were not similar to those of Dmitrovic et al ( 16 ) . This discordance may be because their control group was composed of patients without dysmenorrhea and the differences in the methods used in uterine and cervix measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In group D, the overall state of rats was better than that of group C, and the hair color was glossy and active. Dmitrovic et al found that the uterus of dysmenorrhea women was larger than that of healthy women, especially in the transverse, anterior, and posterior diameters [39]. We wanted to know the relationship between uterine morphology, uterine microvasculature, and uterine prostaglandin.…”
Section: Effect Of Moxibustion On the General State Of Ratsmentioning
confidence: 99%
“…Correspondingly, there is a significant reduction in uterine blood flow associated with the time of maximal pain (Khamis et al, 2003). Studies suggest uterine diameter and endometrial thickness are related to severe primary dysmenorrhea (Dmitrovic, 2004).…”
mentioning
confidence: 99%